Modelling the factors associated with deadweight and displacement: an Irish industrial policy evaluation - Lenihan, Helena (Statistical and Social Inquiry Society of Ireland, 2004)
Evaluating industrial policy interventions has become a growing theme for academics and policymakers. Evaluation should explore the `counter-factual?; this involves examining the related phenomena of deadweight and displacement. Research to date has almost exclusively concerned itself with deriving headline estimates of these phenomena (particularly deadweight in the Irish context) and discussing their consequences. The main argument in this paper is that it is no longer sufficient to merely derive estimates of deadweight and displacement and to discuss their consequences; the focus of attention should now turn to establishing specific firm factors (e.g. size of firm; type of firm ownership; type of assistance received) that influence these estimates. It is only then that real policy improvements and learning can occur. To this end, the explicit focus of this paper is to ascertain whether certain firm characteristics are likely to influence the likelihood of deadweight and/or displacement effects. The methodological approach developed has broadbased applicability beyond the Irish context, given that the econometric techniques adopted are adaptable to the evaluation of various types of policy interventions in a variety of contexts.
Read before the Society, 26 November 2003
Keywords: Deadweight effects; Displacement effects; Industrial policy; Evaluation; 314.15